Parallel 5x step-up SC DC-DC converter for power efficiency improvement - Pongswatd, Sawai; Smerpituk, Krit; Eguchi, Kei; Sasaki, Hirofumi (My University, 2011)
In switched-capacitor converter, the fluctuation of on-resistance effects power efficiency in proportion to the decrease of output load. This paper presents switched-capacitor (SC) DC-DC converter that parallel-connected to improve the power efficiency. The converter utilizes solar energy for industrial wireless transmitter. It can be supplied by its internal battery in combination with the proposed converter for long battery runtime. A Rosemount wireless transmitter from Emerson Process Management Company is used as a target application example in process measurement. The proposed converter is designed for receiving 1.5 V solar cells and powering 7.5 V connect in parallel with wireless transmitter battery. The validity of the theoretical analyses is confirmed by SPICE simulations and experimental results. The derived formulas will be helpful to estimate circuit characteristics. Moreover, SPICE simulation values and experimental results agree well with theoretical results. © 2011 SICE.
Keywords: Converter; parallel-connected; Process Measurement; switched-capacitor circuit; Wireless Transmitter